2008
DOI: 10.1016/j.ultrasmedbio.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Enhanced Thrombolysis Using Definity® as a Cavitation Nucleation Agent

Abstract: Ultrasound has been previously shown to act synergistically with a thrombolytic agent, such as recombinant tissue plasminogen activator (rt-PA) to accelerate thrombolysis. In this in vitro study, a commercial contrast agent, Definity ® , was used to promote and sustain the nucleation of cavitation during pulsed ultrasound exposure at 120 kHz. Ultraharmonic signals, broadband emissions, and harmonics of the fundamental were measured acoustically by using a focused hydrophone as a passive cavitation detector and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
200
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 40 publications
2
200
3
Order By: Relevance
“…Our experimental setup does not allow the investigation of bubble dynamics, that is, whether destruction or oscillation of microbubbles in the sound field (stable cavitations) are most beneficial. An earlier in vitro study suggested that stable cavitation activity may result in strongest treatment effects (Datta et al, 2008). Further investigations need to address this interesting field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Our experimental setup does not allow the investigation of bubble dynamics, that is, whether destruction or oscillation of microbubbles in the sound field (stable cavitations) are most beneficial. An earlier in vitro study suggested that stable cavitation activity may result in strongest treatment effects (Datta et al, 2008). Further investigations need to address this interesting field of research.…”
Section: Discussionmentioning
confidence: 99%
“…In FUS-induced BBB opening, 20,[32][33][34][35][36][37] sonothrombolysis, [38][39][40][41][42] and histotripsy 43,44 studies, correlations between the cavitation activity measured using a single-element passive cavitation detector (PCD) and treatment outcome have been reported. Moreover, microbubble emissions have been used to select treatment pressures 36 and modulate them in real-time between subsequent therapy pulses 35 during FUS-induced BBB opening.…”
Section: Introductionmentioning
confidence: 99%
“…Each frequency spectrum was scaled to account for the energy lost due to windowing. A frequency domain comb filter was applied to the power spectrum ( Figure 3C) to extract the ultraharmonic (100 kHz bands at odd multiples of 500 kHz) and broadband 38,39 This process is depicted graphically in Figure 3.…”
Section: Ultrasound Exposure and Cavitation Detectionmentioning
confidence: 99%